2011
DOI: 10.1021/bi200031m
|View full text |Cite
|
Sign up to set email alerts
|

A Cleavage Enzyme-Cytometric Bead Array Provides Biochemical Profiling of Resistance Mutations in HIV-1 Gag and Protease

Abstract: The majority of protease – substrate assays rely on short, synthetic peptide substrates consisting of native or modified cleavage sequences. These assays are inadequate for interrogating the contribution of native substrate structure distal to a cleavage site that influences enzymatic cleavage or for inhibitor screening of native substrates. Recent evidence from HIV-1 isolates obtained from individuals resistant to protease inhibitors has demonstrated that mutations distal to or surrounding the protease cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…The results presented here advance recent work in the field, using Potts models to study HIV-1 evolution (Barton et al 2016b;Butler et al 2016), by providing systematic prospective predictions quantifying the influence of specific multi-residue patterns on the tolerance of drug resistance mutations. Recent publications have reported that mutations near or distal to Gag cleavage sites play a role in promoting cleavage by drug-resistant and enzymatically deficient proteases, by selecting for mutations that increase substrate contacts with the protease active site, altering the flexibility of the cleavage site vicinity, or by as of yet unknown mechanisms Kolli et al 2009;Breuer et al 2011;Parry et al 2011;Fun et al 2012;Flynn et al 2015). This suggests that viral coevolution of Gag with selective protease mutations may further stabilize multiple resistance mutations; thus, the analysis of protease mutation patterns can be extended to include amino acid substitutions within Gag and the Gag-Pol polyprotein.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here advance recent work in the field, using Potts models to study HIV-1 evolution (Barton et al 2016b;Butler et al 2016), by providing systematic prospective predictions quantifying the influence of specific multi-residue patterns on the tolerance of drug resistance mutations. Recent publications have reported that mutations near or distal to Gag cleavage sites play a role in promoting cleavage by drug-resistant and enzymatically deficient proteases, by selecting for mutations that increase substrate contacts with the protease active site, altering the flexibility of the cleavage site vicinity, or by as of yet unknown mechanisms Kolli et al 2009;Breuer et al 2011;Parry et al 2011;Fun et al 2012;Flynn et al 2015). This suggests that viral coevolution of Gag with selective protease mutations may further stabilize multiple resistance mutations; thus, the analysis of protease mutation patterns can be extended to include amino acid substitutions within Gag and the Gag-Pol polyprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Our detailed understanding of the role of protein processing in the regulation of protein function for the proteins present in Gag is creating opportunities to design assays amenable for use in high throughput screens to search for lead compounds that can inhibit the assembly of an infectious particle (97)(98)(99). The 25 years of studying the biochemistry of the HIV-1 virion was built on an earlier 15 years of studying other retroviruses, starting with the identification of a Gag precursor in avian myeloblastosis virus (100).…”
Section: Looking Aheadmentioning
confidence: 99%
“…In all cases, the aromatic ring is conjugated with an electro deficient heterocycle or an electron-withdrawing group. Through the use of a Gag cytometric bead array assay (Breuer et al, 2011), it was demonstrated that unlike the zinc ejectors, the identified NC inhibitors did not interfere with protease mediated processing of Gag (Breuer et al, 2012). …”
Section: Zinc Finger Bindersmentioning
confidence: 99%
“…Although our group has developed and reported on methods to identify inhibitors of NC and Gag function (Breuer et al, 2012; Breuer et al, 2011), we would like to propose an as of yet unexploited strategy to disrupt NC function utilizing small molecules. We posit that it would be possible to chemically target the NC-nucleic acid complex, where the compound acts as a NC-RNA complex stabilizer, unlike the NC inhibitors identified thus far, which were discussed in the review.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%